Description of faDescription Of Family Knowledge Performing Emergency First Aid For Fever Seizures In Toddlers At The Rami Pematmily knowledge performing emergency first aid for fever seizures in toddlers at the rami pematangsiantar health center in 2021. - Nagoklan Simbolon; Indra Hizkia; Agnes Tabita Tampubolon (Institute of Computer Science (IOCS), 2022)
Knowledge The right first treatment that mothers can do when their child has a febrile seizure is to stay calm and don't panic, try to lower the child's bodytemperature, position the child correctly, namely the child's head is tilted, placed in a flat place, away from objects or actions that can injure children.. Fever seizures are seizures that occur when the body temperature rises (rectal temperature above 38°C) caused by extracranial processes. Febrile seizures are seizures that occur when the body temperature rises (rectal temperature above 38°C) caused by extracranial processes. The prevalence of febrile seizures in children under 5 years of age occurs every year in America, nearly 1.5 million people. The incidence of febrile seizures varies in different countries. The annual incidence of febrile seizures is 2-4% in Western Europe and America, 5-10% in India and 8.8% in Japan. Simple febrile seizures are 80% of all febrile seizures. Emergency in toddlers with febrile seizures at the Rami Pematangsiantar Health Center in 2021. Descriptive research that results from the study obtained good knowledge of 10 people (22.2%) and at most 22 people (48.9%) and less than 13 people (28.9). %). Another thing is because of the lack of information, health education only focuses on household matters without knowing how to maintain the health and safety of children.